Peran Literasi Keuangan dalam Penguatan Kapasitas Usaha dan Pembangunan Ekonomi Inklusif UMKM di Kota Bima: Indonesia - Aris Munandar; Nurul Huda; Rini Uswatun (Fakultas Ekonomi Universitas Islam 45, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Bima City play a vital role in the local economy; however, limited financial literacy remains a major barrier to effective and sustainable business management. This study aims to analyze the role of financial literacy in strengthening business capacity and fostering an inclusive community-based economy. A quantitative approach with an explanatory survey design was employed, involving 120 MSME actors purposively selected based on business experience and participation in entrepreneurship training. Data were collected through a five-point Likert scale questionnaire covering financial literacy, MSME empowerment, and inclusive economy variables. Data analysis using SEM-PLS revealed that financial literacy has a significant effect on MSME empowerment and inclusive economy, both directly and indirectly through partial mediation of MSME empowerment. The findings highlight that mastering basic financial concepts, cash flow planning, and utilizing formal financial services substantially enhance business capacity and broaden participation in a fair economic system. Therefore, integrating financial literacy into MSME empowerment programs in Bima City is essential to strengthen local competitiveness and accelerate sustainable economic growth.